2022
DOI: 10.54986/irjee/2022/jan_mar/81-85
|View full text |Cite
|
Sign up to set email alerts
|

Role of Psychological Attributes of DAESI Dealers in Knowledge and Skill Development

Abstract: Psychological attributes are the internal human characteristics which reflect a great impact over the trainees of any programmme. These attributes are distinct for each and everyone. National Institute of Agricultural Extension Management (MANAGE) had launched a individual financed One-year Diploma in Agricultural Extension Services for Input Dealers (DAESI) Programme during the year 2003 for the input dealers in order to make input dealer competent enough in terms of knowledge and skill. In Chhattisgarh, unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
0
0
Order By: Relevance
“…These findings align with the study conducted by Staudacher et al (2021), which reported that a significant percentage of agro-dealers had received instructions on pesticide application, indicating a level of competence in chemical administration. Additionally, Handa et al (2021) found that agro-dealers demonstrated medium to high levels of communication attributes, including the regular utilization of newspapers, mobile phones, and mass media. Furthermore, Table 3 presents the results of the Wilcoxon Signed Rank Test, which evaluates the proficiency and significance of agro-dealers' skills.…”
Section: Discrepancy In Agro-dealers' Skillsmentioning
confidence: 99%
“…These findings align with the study conducted by Staudacher et al (2021), which reported that a significant percentage of agro-dealers had received instructions on pesticide application, indicating a level of competence in chemical administration. Additionally, Handa et al (2021) found that agro-dealers demonstrated medium to high levels of communication attributes, including the regular utilization of newspapers, mobile phones, and mass media. Furthermore, Table 3 presents the results of the Wilcoxon Signed Rank Test, which evaluates the proficiency and significance of agro-dealers' skills.…”
Section: Discrepancy In Agro-dealers' Skillsmentioning
confidence: 99%